DOI: 10.11606/d.10.2009.tde-08122009-114630
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento adicional da acidose láctica ruminal aguda em bovinos por meio de infusão de solução salina hipertônica (7,2%)

Abstract: Ao Prof. Dr. Enrico Ortolani, pelos ensinamentos passados, por me dar a oportunidade de participar desta família desde a graduação, pelo seu esmero e dedicação com seus orientados e alunos egressos, bem como, a esta Instituição e a classe veterinária. Sua percepção midiática me desperta admiração. Homenageá-lo Paraninfo foi único e teve um significado especial para mim. Aos meus irmãos da família Ortolani: é inefável a gratidão por tudo que vocês fizeram por mim, não só pela execução deste laborioso experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
1
1
0
3
Order By: Relevance
“…These signs was observed when ruminal pH values are near or lower than 5.0. The time frames detected in our study corroborate with findings of several studies on experimentally induced ALRA in cattle, which reported that the onset of signs occurred between 9 and 72h after induction, depending on the protocol adopted (Ortolani 1995, Brown et al 2000, Momcilovic et al 2000, Thoefner et al 2004, Danscher et al 2009, Rodrigues 2009). …”
Section: Discussionsupporting
confidence: 90%
“…These signs was observed when ruminal pH values are near or lower than 5.0. The time frames detected in our study corroborate with findings of several studies on experimentally induced ALRA in cattle, which reported that the onset of signs occurred between 9 and 72h after induction, depending on the protocol adopted (Ortolani 1995, Brown et al 2000, Momcilovic et al 2000, Thoefner et al 2004, Danscher et al 2009, Rodrigues 2009). …”
Section: Discussionsupporting
confidence: 90%
“…As in this study we did not measured ruminal pH, we intended to estimate a condition of lactacidemia, based on the measurement of blood lactate. Rodrigues (2009) correlated ruminal pH and ruminal concentrations of lactate in cattle, observing a high negative correlation between these two variables (R 2 =0.9127). The same author correlated ruminal lactate and blood lactate, noting a significant positive correlation between the two variables (R 2 =0.718).…”
Section: Discussionmentioning
confidence: 89%
“…Os trabalhos resultantes do modelo de indução com sacarose também não especificaram a relação dos sintomas que mais estiveram envolvidos com a necessidade de tratamento (MENDES NETTO, 1997;MARUTA, 2000, LEAL et al, 2007RODRIGUES, 2009;ORTOLANI et al, 2010).…”
Section: Virginiamicinaunclassified
“…Densidade urinaria (7 Ortolani (1995), visto que em empregos anteriores do protocolo não foram estudadas variáveis como os ácidos graxos de cadeia curta (AGCC), teores de glicose ruminal, potencial de oxido-redução e total de ácidos orgânicos ruminais, além do fato que até então não se tinha estudado estas e outras variáveis precocemente nas primeiras 12 h do protocolo (MENDES NETTO, 1997;MARUTA, 2000, LEAL et al, 2007RODRIGUES, 2009).…”
Section: Concentração De Lactato -D Na 18ª H Dos Animais Tratados E Dunclassified